2001
DOI: 10.1007/s001920170016
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Configuration on MRI after Abdominal Sacrocolpopexy and Sacrospinous Ligament Suspension

Abstract: An MRI study was conducted to compare the vaginal configuration of women who had undergone sacrospinous fixation with transvaginal needle suspension or abdominal sacrocolpopexy with retropubic colposuspension with that of normal controls. MRI examination demonstrated that in normal controls the lower vagina formed an acute angle (mean 53 degrees) with the pubococcygeal line and intersected the upper vagina at a mean angle of 145 degrees. In the abdominal repair group the lower vagina intersected the pubococcyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 11 publications
(19 reference statements)
1
44
0
2
Order By: Relevance
“…[12][13][14] During our preparatory dissections, we observed that the S4 foramen, which is found on the lowest border of the S4 vertebra, was more accurately and consistently identified in cadavers than the tip of the coccyx; therefore, we chose the S4 foramen instead of the coccyx in an attempt to increase reproducibility of our measurements. The vaginal axis angle was then measured from the PS-S4 line to each to each vertebral point and recorded using a 15 cm orthopedic goniometer (Quint Measuring Systems, Inc., San Ramon, CA) ( Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14] During our preparatory dissections, we observed that the S4 foramen, which is found on the lowest border of the S4 vertebra, was more accurately and consistently identified in cadavers than the tip of the coccyx; therefore, we chose the S4 foramen instead of the coccyx in an attempt to increase reproducibility of our measurements. The vaginal axis angle was then measured from the PS-S4 line to each to each vertebral point and recorded using a 15 cm orthopedic goniometer (Quint Measuring Systems, Inc., San Ramon, CA) ( Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Because it has proven its efficacy in vaginal vault prolapse surgery, it might be of interest to use it as a primary technique to correct descensus uteri, the so-called sacrospinous hysteropexy. The anatomical outcome and complication rate of this operation was described in few reports, but most authors do not focus on urogenital symptoms and quality of life after sacrospinous hysteropexy [3][4][5][6][7][8]. In a previous study by our group, we concluded that the sacrospinous hysteropexy is a promising technique for the correction of descensus uteri [9].…”
Section: Introductionmentioning
confidence: 96%
“…The anatomic restoration is profoundly important in pelvic reconstructive surgery. MRI studies showed that ASC produces a vaginal axis closer to the original anatomic position than SSF (34).…”
Section: Discussionmentioning
confidence: 97%
“…Unilateral SSF appears satisfactory, with a low recurrence rate, but is associated with the anatomical distortion of the vagina and the rectum that may alter both sexuality and bowel function (11,14). Furthermore, some authors hypothesize that the higher POP recurrence and dyspareunia rates after unilateral SSF may be due to a posterior deviation of the vaginal axis and a tensioned repair with surgeons using permanent sutures during a unilateral SSF (15,16). Because of these reasons, some authors recommend bilateral SSF, and a few studies including small number of patients have focused on anatomical and functional results after bilateral SSF (17-21).…”
Section: Discussionmentioning
confidence: 99%